ANALISIS HUBUNGAN PENERAPAN PROBLEM BASED LEARNING DENGAN SELF DIRECTED LEARNING MAHASISWA - Novitasari, Novitasari; Listiawati, Rodiana; Redyanita, Hastuti; Ihsan, Muhamad (Jurnal Muara Pendidikan, 2024)
Soft skills that are expected to emerge in students in the form of independent learning behavior, initiative and exploration (Self Directed Learning) have not been seen in learning that uses classical methods in the form of lectures and assignments only. To overcome this problem, a problem-based learning model or Problem Based Learning (PBL) was applied to the Finance and Banking Study Program of the Jakarta State Polytechnic. This study aims to determine and analyze the relationship between the application of Problem Based Learning (PBL) and students' Self Directed Learning (SDL) abilities. The research methodology used is descriptive quantitative research, with primary data collection techniques in the form of questionnaires. To test the relationship between the application of PBL and SDL using the Pearson Correlation test. The results of the study showed that there was a positive relationship or correlation between the application of Problem Based Learning and students' Self Directed Learning abilities. The results of this study are useful in the world of education, especially higher education, to be able to apply problem-based learning because it can improve the quality of student learning, and is able to foster creative and innovative student characters.